Progress Report: Status of items on the 1975-76 National Legislative Platform (1976)
This February 20, 1976 progress report from the National Federation of Business and Professional Women's Clubs reviews the status of its 1975–76 legislative platform, focusing on women's rights, equality, and public policy. It updates members on the Equal Rights Amendment, Title IX enforcement, equal employment and pension benefits, credit discrimination reforms, Social Security inequities, child care tax credits, child and family services legislation, and federal civil service political participation under the Hatch Act. The report also summarizes pending and enacted legislation related to health services, aging, disabilities, rape law reform, displaced homemakers, environmental policy, and the proposed creation of a National Center for Women. A concluding section presents statistics demonstrating the severe underrepresentation of women in public office and government leadership, underscoring the continuing need for political and legal reform.